Pengaruh Selebriti Pendukung, Strategi Diferensiasi, Dan Citra Merek Terhadap Keputusan Pembelian Produk Vivo Smartphone (Studi Kasus Pada Mahasiswa Program Sarjana Institut Stiami Jakarta Pusat Tahun Angkatan 2015-2018) - Iis Nur Faridah; Hartono Hartono; Nur Fitri Rahmawati (JAMBIS : Jurnal Administrasi Bisnis, 2021)
This study aims to analyze the influence of celebrities endorser, differentiation strategies, and brand image on the decision to purchase Vivo Smartphone products for the 2015-2018 bachelor degree students of Stiami Institute Central Jakarta. The population in this study were all bachelor's degree students at Stiami Institute Central Jakarta in the year 2015-2018. The sampling technique used was non-probality sampling with a type of purposive sampling technique and a total sample of 100 respondents. Data collection has done by giving questionnaires to students’ using Smartphone Vivo products about celebrities endorser, differentiation strategies, brand image, and purchasing decisions. This study uses a multiple linear regression and coefficient of determination, with a measuring instrument, namely SPSS version 24. The hypothesis is tested by t-test and F test. The test results show that celebrity endorser, differentiation strategies, and brand image partially have a significant positive effect on decision purchase. As well as celebrities endorser, differentiation strategies, and brand image simultaneously have a significant positive effect on purchasing decisions. Celebrities endorsers, differentiation strategies, and brand image can explain purchasing decision variables of 62.2% while the remaining 37.8% are explained by other variables not examined. Keywords: Celebrities Endorser, Differentation Strategies, Brand Image, Purchase Decisions